Interactive Effects of Mycorrhizae, Soil Phosphorus, and Light on Growth and Induction and Priming of Defense in Plantago lanceolata - Qu, Laiye; Wang, Minggang; Biere, Arjen (Frontiers in Plant Science, 2021)
Increasing demands to reduce fertilizer and pesticide input in agriculture has triggered interest in Arbuscular Mycorrhizal Fungi (AMF) that can enhance plant growth and confer Mycorrhiza-induced Resistance (MIR). MIR can be based on a variety of mechanisms, including induction of defense compounds, and sensitization of the plant’s immune system (priming) for enhanced defense against later arriving pests or pathogens signaled through jasmonic acid (JA). However, growth and resistance benefits of AMF highly depend on environmental conditions. Low soil P and non-limiting light conditions are expected to enhance MIR, as these conditions favor AMF colonization and because of observed positive cross-talk between the plant’s phosphate starvation response and JA-dependent immunity. We therefore tested growth and resistance benefits of the AMF Funneliformis mosseae in Plantago lanceolata plants grown under different levels of soil P and light intensity. Resistance benefits were assessed in bioassays with the leaf chewing herbivore Mamestra brassicae. Half of the plants were induced by jasmonic acid prior to the bioassays to specifically test whether AMF primed plants for JA-signaled defense under different abiotic conditions. AMF reduced biomass production but contrary to prediction, this reduction was not strongest under conditions considered least optimal for carbon-for-nutrient trade (low light, high soil P). JA application induced resistance to M. brassicae, but its extent was independent of soil P and light conditions. Strikingly, in younger plants, JA-induced resistance was annulled by AMF under high resource conditions (high soil P, ample light), indicating that AMF did not prime but repressed JA-induced defense responses. In older plants, low soil P and light enhanced susceptibility to M. brassicae due to enhanced leaf nitrogen levels and reduced leaf levels of the defense metabolite catalpol. By contrast, in younger plants low soil P enhanced resistance. Our results highlight that defense priming by AMF is not ubiquitous and calls for studies revealing the causes of the increasingly observed repression of JA-mediated defense by AMF. Our study further shows that in our system abiotic factors are significant modulators of defense responses, but more strongly so by directly modulating leaf quality than by modulating the effects of beneficial microbes on resistance.